Reader’s Factors in Interpreting Eldorado by Edgar Allan Poe Using Reader-Response Theory: A Preliminary Study - Risa R. Simanjuntak; Lia Kristianti Joelianto (Bina Nusantara University, 2011)
Article aims to find variety of interpretations on Eldorado poem, following the readers’ internal factors, such as societal norms, personal values and past experiences influence the interpretations. Data generated for this study are acquired through field research, in which questionnaires are used as data collecting instrument. The respondents are from third semester students of English Literature in Bina Nusantara University. The finding shows that interpretations of Eldorado include 44% ideas about failure, 24% ideas about perseverance, and 25.33% ideas about taking a journey. In comparison to Eldorado’s more neutral interpretation, it could be said that more respondents prefer to discuss the poem as the journey of life. It can be concluded that different societal norms, personal values and past experiences cause different kinds of interpretations, in which past experience becomes the most influential factor.